Recycling of industrial by-products in concrete: Experimental study. Issue 1 (September 2021) - Hussian, R.; Adnan, A.
Abstract: The construction industry consumes enormous amounts of ordinary Portland cement (OPC) to bond the fine and coarse aggregates that give the concrete strength. However, the OPC causes many environmental severe impacts, such as the huge generation of CO2 gas and alkaline wastewater, which triggered concerns about the health consequences of OPC manufacturing. Therefore, the search for eco-friendly alternatives for OPC has increased rapidly during the last decades, such as the recycling of agricultural and industrial by-products. In this research, residuals of cement furnaces (the dust of cement furnace) and silica fume were mixed and the latter was used as a partial replacement for the OPC. Initially, the chemical structure of the cement dust, silica fume and the OPC were tested. Then, three different (0-45%) percentages of the cement dust and silica fume were added to the concrete mix. The mechanical properties of the produced concrete were investigated using a non-destructive method (ultrasonic pulse velocity) and compared with the properties of the traditional OPC concrete. The results showed the cement dust and silica fume contain the favourable oxides, and the best mixing ratio was 12.5% of silica fume, 12.5% of cement dust and 75% of OPC that achieved pulse velocity of 4102 m/s (the best compressive strength).